Employee Work Discipline at the Baraka District Office, Enrekang Regency - Pirda, Pirda; Akib, Haedar; Nasrullah, Muh. (Journal of Public Policy and Local Government (JPPLG), 2024)
This study aims to find out the work discipline of employees at the Baraka District Office, Enrekang Regency. By using qualitative research methods with descriptive research types. The data collection technique uses observation, interview, and documentation methods. The data analysis techniques used are data collection, data presentation, data condensation and conclusion/verification. The results of the study show that each indicator used can be said to be "good" according to the indicators used, namely Attendance, employee attendance is quite good because employees are present on time to the office. Compliance with work regulations, employees implement work regulations in accordance with Standard Operating Procedures (SOPs) properly. Regulations on work standards, employees have implemented work standards well. Working ethically, judged from the level of employee ethics, both fellow employee leaders and the community. Therefore, employee work discipline can be said to be quite good and there are performance achievements that must be fulfilled by employees, otherwise employees will be subject to sanctions. This research also uses the latest indicators regarding employee discipline and is supported by the latest journals and supporting books